The Effect of Obesity in Pregnancy and Gestational Weight Gain on Neonatal Outcome in Glucose-Tolerant Mothers - Loh, Huai Heng; Haslinda, Taipin; Asri, Said (John Wiley & Sons, Inc, 2021)
Most studies showing association between mothers with obesity in pregnancy or excessive gestational weight gain (GWG) and adverse neonatal outcome were cross-sectional or retrospective. Many included patients with gestational diabetes mellitus (GDM), which is a strong risk factor for this adverse outcome. There are no prospective studies on this topic in Malaysia. This study aimed to examine prospectively the effect of obesity in pregnancy and GWG, independent of GDM, on neonatal outcome.